Workshop: Tobacco Control Research under Digitalization - Chen, Yu; Zhang, Jinxiang (The Journal of Medicine, Humanity and Media, 2023)
A particular focus of attention was the "Tobacco Control Research Workshop," led by Assistant Professor Lin Haoxiang from the Institute of Global Health and Development, Peking University. The workshop featured review from Assistant Professor Yang Fan of the Institute of Population Research, Peking University and Associate Professor Pan Wenjing of the School of Journalism and Communication at Renmin University of China. Dr. Cheng Cheng from the University of Lisbon, Yu Chen, a Ph.D. student at the School of Journalism and Communication, Peking University, Xindou Chen, an undergraduate student at respective, and Ziliang Wang, an undergraduate student at the Public Health School of Health Science Center, Peking University, respectively presented their latest research on tobacco control.